Re-engineering cellular physiology by rewiring high-level global regulatory genes - DORMAN, CHARLES (My University, 2015)
Knowledge of global regulatory networks has been exploited to rewire the gene control programmes of the model bacterium Salmonella enterica serovar Typhimurium. The product is an organism with competitive fitness that is superior to that of the wild type but tuneable under specific growth conditions. The paralogous hns and stpA global regulatory genes are located in distinct regions of the chromosome and control hundreds of target genes, many of which contribute to stress resistance. The locations of the hns and stpA open reading frames were exchanged reciprocally, each acquiring the transcription control signals of the other. The new strain had none of the compensatory mutations normally associated with alterations to hns expression in Salmonella; instead it displayed rescheduled expression of the stress and stationary phase sigma factor RpoS and its regulon. Thus the expression patterns of global regulators can be adjusted artificially to manipulate microbial physiology, creating a new and resilient organism.
Keywords: bacterium Salmonella enterica serovar Typhimurium; bacterium Salmonella enterica serovar Typhimurium; Genes & Society; Immunology, Inflammation & Infection